Hybrid supramolecular gels of Fmoc-F/halloysite nanotubes: systems for sustained release of camptothecin12. Issue 17 (13th April 2017) - Rizzo, C.; Arrigo, R.; D'Anna, F.; Di Blasi, F.; Dintcheva, N. T.; Lazzara, G.; Parisi, F.; Riela, S.; Spinelli, G.; Massaro, M.
Abstract : Novel supramolecular gel hybrids were prepared by self-assembly of Fmoc-l -phenylalanine in the presence of functionalized halloysite nanotubes and employed as carriers for the delivery of camptothecin molecules. Abstract : Supramolecular gel hybrids obtained by self-assembly of Fmoc-l -phenylalanine (Fmoc-F) in the presence of functionalized halloysite nanotubes (f-HNT) were obtained in biocompatible solvents and employed as carriers for the delivery of camptothecin (CPT) molecules. The synthesis of the new f-HNT material as well as its characterization are described. The properties of the hybrid hydrogels and organogels were analyzed by several techniques. The presence of small amounts of f-HNT allows good dispersion of the tubes and the subsequent formation of homogeneous gels. The experimental results show that f-HNT functions only as an additive in the hybrid gels and does not demonstrate gelator behavior. The in vitro kinetic release from both f-HNT/CPT and Fmoc-F/f-HNT/CPT was studied in media that imitates physiological conditions, and the factors controlling the release process were determined and discussed. Furthermore, the antiproliferative in vitro activities of the gels were evaluated towards human cervical cancer HeLa cells. A comparison of data collected in both systems shows the synergistic action of f-HNT and the gel matrix in controlling the release of CPT in the media and maintaining the drug in its active form. Finally, a comparison with pristine HNT is also reported. This study suggests a suitable strategy to obtain two-component gel hybrids based on nanocarriers with controlled drug carrier capacity for biomedical applications.